Effect of Home-Based Cardiac Rehabilitation in a Lower-Middle Income Country: RESULTS FROM A CONTROLLED TRIAL. Issue 1 (January 2020) - Uddin, Jamal; Joshi, Vicky L.; Moniruzzaman, Mohammad; Karim, Rezaul; Uddin, Jalal; Siraj, Masoom; Rashid, Mohammad Abdur; Rossau, Henriette Knold; Taylor, Rod S.; Zwisler, Ann-Dorthe
Abstract : Purpose: Cardiovascular disease is the leading cause of mortality and morbidity in lower-middle income countries (LMICs), including Bangladesh. Cardiac rehabilitation (CR) as part of secondary prevention of cardiovascular disease has been shown to reduce mortality and morbidity and improve quality of life and exercise capacity. However, to date, very few controlled trials of CR have been conducted in LMICs. Methods: A quasi-randomized controlled trial comparing home-based CR plus usual care with usual care alone was undertaken with patients following coronary artery bypass graft surgery. Participants in the CR group received an in-hospital CR class and were introduced to a locally developed educational booklet with details of a home-based exercise program and then received monthly telephone calls for 12 mo. Primary outcomes were coronary heart disease (CHD) risk factors, health-related quality of life (HRQOL), and mental well-being. Maximal oxygen uptake as a measure of exercise capacity was a secondary outcome. Results: In total, 142 of 148 eligible participants took part in the trial (96%); 71 in each group. At 12-mo follow-up, 61 patients (86%) in the CR group and 40 (56%) in the usual care group provided complete outcome data. Greater reductions in CHD risk factors and improvements in HRQOL, mental well-being, and exercise capacity were seen for the CR group compared with the usual care group. Conclusions: In the context of a single-center LMIC setting, this study demonstrated the feasibility of home-based CR programs and offers a model of service delivery that could be replicated on a larger scale. Abstract : Supplemental Digital Content is Available in the Text.A quasi-randomized controlled trial comparing home-based cardiac rehabilitation with usual care was undertaken with patients following coronary artery bypass graft surgery in Bangladesh, a lower- to middle-income country. The trial found cardiac rehabilitation was feasible and provided similar patient benefits to trials of cardiac rehabilitation based in high-income countries.